BUDAYA TOLERANSI ORANG BALI DALAM NASKAH KUNO GEGURITAN SUCITA MUAH SUBUDHI - Purna, I Made (Puslitjakdikbud Balitbang Kemdikbud, 2016)
AbstractSince the earliest time, Indonesian has become a multicultural nation with diverse tribes,traditions, local languages, and religions. Thus, it is necessary to have a local wisdom thatcontains tolerance values and teaches respect towards ethnic diversity. Included in this case islocal wisdom that based on an ancient manuscript. The tolerant lifestyle among religious andethnic differences in Balinese community has been managed in the form of an ancient manuscriptGeguritan Sucita Muah Subudhi. This paper has three objectives: first, to explain the values inthe Geguritan Sucita Muah Subudhi; second, to describe the actualization form of toleranceimplemented by the Balinese; and third, to expose the functions Geguritan Sucita Muah Subudhiin Balinese society. The method used in this study is content analysis. The main process to obtaindata is through ancient manuscripts Geguritan Sucita Muah Subudhi, related researches andother relevant information. The results shows that tolerance in Bali is performed well. It evenabsorbs cultural elements from various religions and ethnicities in the land of Bali. Tolerancelifestyle can be actualized through traditional organizations and social activities, as well asarranged through the concepts of local wisdom.Keywords: tolerance, religion, multiculture, brotherhood.AbstrakSejak zaman dahulu bangsa Indonesia sudah menjadi bangsa multikultur dengan beragamsuku, tradisi, bahasa daerah dan agama yang berbeda-beda. Untuk itu diperlukan kearifanlokal yang mengandung nilai-nilai toleransi dan saling menghargai atas keberagaman etnis.Termasuk dalam hal ini kearifan lokal yang bersumber dari naskah kuno. Pengelolaan polahidup toleran antara penganut yang berbeda agama maupun etnis pada masyarakat Bali sudahdituangkan dalam bentuk naskah kuno Geguritan Sucita Muah Subudhi. Tulisan ini mempunyaitiga tujuan: Pertama, memaparkan nilai-nilai dalam lontar Geguritan Sucita Muah Subudhi;kedua, memaparkan tentang bentuk aktualisasi toleransi yang dilaksanakan oleh Orang Bali;ketiga, memaparkan fungsi Geguritan Sucita Muah Subudhi dalam masyarakat Bali. Metodeyang digunakan adalah analisis isi (content analysis). Proses pengambilan data yang utamamelalui naskah kuno Geguritan Sucita Muah Subudhi dan hasil penelitian serta informasi yangrelevan lainnya. Hasil penelitian menunjukkan bahwa toleransi di Bali berjalan baik. Bahkansaling menyerap unsur budaya yang dibawa dari berbagai agama dan etnik yang ada di tanahBali. Hidup toleransi dapat diaktualisasikan pembuktianya melalui organisasi tradisional, dankegiatan sosial, serta ditata melalui konsep-konsep kearifan lokal.Kata Kunci: toleransi, agama, multikultural, nyama